Practitioner perspectives on the nexus between acquired brain injury and family violence. (29th May 2019) - Pritchard, Elizabeth; Tsindos, Tess; Ayton, Darshini
Abstract: Family violence has been highlighted by the World Health Organization as a major public health concern. Although family violence occurs to all genders, a higher prevalence of victims are female. Estimates report around 30% of all women experience intimate partner violence worldwide. Experiencing assault in the family violence context can lead to an acquired brain injury (ABI); however, the connection between these two phenomena has not been well established. The aim of this qualitative study was to explore the extent of, and factors contributing to, ABI and family violence. We conducted 22 semi‐structured interviews and one focus group ( n  = 4) with practitioners working with family violence victims and/or perpetrators. Thematic data analysis utilised inductive and deductive coding approaches. The Social Determinants of Health Framework was used to guide analysis. Practitioners estimated 30%–40% of the clients on their caseloads had a suspected or diagnosed ABI. They identified that contributing factors were extremely complex. These included acquiring an ABI through assault (past family violence or other criminal act), and transport crashes. Complicating factors of ABI were identified as mental health conditions, alcohol and drug use, and post‐traumatic stress disorder. Additional factors contributing to family violence were recognised as biological (age of parent, twin births, pregnancy, premature births, and children with congenital abnormalities), relationships (intimate partner, father, boyfriend, mother and siblings), previous trauma (family violence), and life stressors (unemployment, financial, and lack of housing). Social determinants of health included cultural (ethnicity, societal attitudes, values, and beliefs) and organisational (legislation and policy) factors which influenced behaviours and outcomes across all sectors. A model of Brain injury Family violence Nexus (BFN) was created to understand the interaction between these phenomena. Utilising the BFN model to understand the interaction can enhance the methods used within health and social services for a more efficacious approach.